Pregnancy suppresses neuropathic pain induced by chronic constriction injury in rats through the inhibition of TNF-α - Onodera, Yoshiko (J Pain Res, 2017)
PURPOSE: Pregnancy-induced analgesia develops during late pregnancy, but it is unclear whether this analgesia is effective against neuropathic pain. The detailed molecular mechanisms underlying pregnancy-induced analgesia have not been investigated. We examined the antinociceptive effect of pregnancy-induced analgesia in a neuropathic pain model and the expression of tumor necrosis factor (TNF)-α, glial fibrillary acidic protein (GFAP), Iba-1, and c-Fos in the spinal dorsal horn just before parturition. MATERIALS AND METHODS: Female Sprague Dawley rats (200–250 g) were randomly assigned to one of four groups (pregnant + chronic constriction injury [CCI]; pregnant + sham injury; not pregnant + CCI; and not pregnant + sham injury). Separate groups were used for the behavioral and tissue analyses. CCI of the left sciatic nerve was surgically induced 3 days after confirming pregnancy in the pregnancy group or on day 3 in the not pregnant group. The spinal cord was extracted 18 days after CCI. TNF-α, GFAP, Iba-1, and c-Fos expression levels in the spinal dorsal horn were measured by Western blot analysis. Mechanical threshold was tested using von Frey filaments. RESULTS: The lowered mechanical threshold induced by CCI was significantly attenuated within 1 day before parturition and decreased after delivery. TNF-α expression in CCI rats was decreased within 1 day before parturition. Further, GFAP, Iba-1, and c-Fos expression in the spinal dorsal horn was reduced in the pregnant rats. Serum TNF-α in all groups was below measurable limits. CONCLUSION: Our findings indicate that pregnancy-induced analgesia suppresses neuropathic pain through reducing spinal levels of TNF-α, GFAP, Iba-1, and c-Fos in a rat model of CCI.